Analysis of GPS and GSM with GPRS-based vehicle tracking and monitoring system - Mohamad Aiman, Mohamad Sharif; Nurul Mubinah, Suhaimi; Muhammad Aizzat, Zakaria (Penerbit UMP, 2024)
Vehicle security has become a major concern in today's world. Due to the increasing number of vehicle thefts, GSM and GPS-based vehicle tracking systems have gained attention to help users keep track of their vehicles. The main objective of this study is to develop an accurate and reliable device to support vehicle owners in tracking the whereabouts of their vehicles. Such devices will allow vehicles to be tracked remotely from a distance by utilizing the already available mobile networks. Specifically, the system will use the GPS (Global Positioning System) Module to collect the vehicle coordinates (latitude and longitude) and send them to the user's mobile upon request, which also allows for the expansion of knowledge on GPS (Global Positioning System), GSM (Global Systems for Mobile) and GPRS (General Packet Radio Service) technology, as well as the SIM interface. It will take some analysis to make this endeavour succeed. A Google Spreadsheet will be used as a database to store the location data from GPS sensors, and information will be sent to it via a connection to the General Packet Radio Service (GPRS) network system. The information will be synced and shown on a visual map so that the user can simply access and track the whereabouts of the vehicle. There is a discussion concerning the accuracy of the GPS sensor being utilised over several places, including urban and rural areas, to determine the device's accuracy. The system's dependability and ability to perform well based on the data collected also have both been studied and analysed. As a result, this paper offers a well-presented study to develop a tracking system to determine the time and position of the monitoring vehicle.